Invented spelling activities in small groups and early spelling and reading - Martins, Margarida Alves (2016)
Our aim was to assess the impact of an invented spelling programme conducted in small groups on children’s written language acquisition in Portuguese. We expected the experimental group to have better post-test results than the control group in spelling and reading. Participants were 160 preschool-age children who were randomly divided into an experimental and a control group. Their age, cognitive ability, knowledge of letters and phonological abilities were controlled. Children’s spelling and reading were evaluated in a pre- and a post-test. Inbetween, experimental group participated in an invented spelling programme in small groups and the control group in story readings. The experimental group showed better results in spelling and reading in the post-test than the control one. Different dynamics occurred in the small groups which had different impacts on children’s acquisitions. These results provide empirical support for the proposal that invented spelling should be incorporated into early literacy instruction.